HUBUNGAN SPIRITUALITAS DENGAN TINGKAT KECEMASAN KELUARGA PASIEN DI RUANG INTENSIF RUMAH SAKIT SANTA ELISABETH MEDAN TAHUN 2015 - Lilis Novitarum (Elisabeth Health Jurnal, 2016)
Spirituality was the unifying aspect and the aspect of integration in a person's life to nature and the Creator. A holistic approach to the spiritual function can affect human welfare. Anxiety is a feeling of fear and consciousness accompanied by physical sensations such as palpitations, shortness of breath or chest pain, this will be experienced by the patient with the family. Intensive patient's family are those who have a relationship with the patient is the father, mother, or sister who still have blood relations with patients. Goal: The purpose of this study identifies the relationship of spirituality to family anxiety levels of patients in the Intensive Space Santa Elisabeth Hospital Medan in 2015. Methods: This research uses design korelation with the type of cross-sectional research, 19 research samples using purposive sampling, data collection and analysis of data in the form of a questionnaire conducted by the Spearman rank test. Result: The survey results revealed the majority (68.4%) patients had a level of spirituality family well and most (57.9%) families of patients have mild anxiety levels. Analysis of the data showed 0.943 alpha r very reliable because the value is greater than 0.60. Based on the test Spearman rank correlation coefficient = - 0.692 obtained and p value = 0.001(p <0.05) this value indicates a strong relationship and a negative pattern means there is a significant relationship with the level of anxiety spirituality where the better the spirituality of the family, the lower anxiety experienced. Conclusion: Expected nurses can provide spiritual care to patients and families of patients in the Intensive Santa Elisabeth Hospital Medan.